2019
DOI: 10.1002/slct.201801668
|View full text |Cite
|
Sign up to set email alerts
|

An Amphiphilic Mesoporous Polymer Comprising a “built‐in” Imidazolium Ionic Liquid via Nanocasting Method as a Novel Catalyst Support with Combined Prospects

Abstract: An imidazolium based ionic liquid bearing triethylene glycol (TEG) tag was employed as a functional monomer together with divinylbenzene to prepare a novel hydrophilic mesoporous polymer containing ionic liquid functionalities via nanocasting method using SBA‐15 as a hard template. The material was characterized using transmission electron microscopy (TEM), N2 sorption analysis, thermo‐gravimetric analysis (TGA), Fourier‐transform infrared spectroscopy (FT‐IR), elemental analysis (CHN), solid‐state NMR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…[24,25] The liquid-liquid biphasic catalysis system has received much attention, and the possibility of using this technology in industrial processes is being investigated by many researchers. [15,26] In recent decades the ILs have attracted much attention because of their extensive applications in organic synthesis, [27][28][29][30][31][32][33] catalytic oligomerization of ethylene, [4,17,25] chemical separation, [34][35][36] material, and energy science. [37,38] For example, the chloroaluminate IL has been used as solvents in ethylene oligomerization reactions in the presence of nickel complexes to overcome the deactivation of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] The liquid-liquid biphasic catalysis system has received much attention, and the possibility of using this technology in industrial processes is being investigated by many researchers. [15,26] In recent decades the ILs have attracted much attention because of their extensive applications in organic synthesis, [27][28][29][30][31][32][33] catalytic oligomerization of ethylene, [4,17,25] chemical separation, [34][35][36] material, and energy science. [37,38] For example, the chloroaluminate IL has been used as solvents in ethylene oligomerization reactions in the presence of nickel complexes to overcome the deactivation of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the control of the hydrophobic/hydrophilic balance in solid catalysts might influence their catalytic performance especially in reactions involving both hydrophobic and hydrophilic reaction partners. Along the line in this hypothesis and with our continuous interest in the tuning and optimization of the hydrophobic/hydrophilic characteristic of catalysts to develop more selective catalysts in recent years, 11 herein, among other possibilities, our purpose is to utilize either ethane-bridged PMO based sulfonic acid ( 1a ) or SBA-15-PrSO 3 H ( 1b ) (Fig. 2) as the catalyst having different surface hydrophobicity in the preparation process of various types of 2-substituted benzoazoles.…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, it was revealed that the presence or absence of plugs inside the mesochannels of BFPMO-IL and simultaneously tuning the hydrophobic/hydrophilic nature of the pores could strikingly affect the selectivity of the reaction toward the formation of aldehydes or carboxylic acids as the main reaction product. 90 However, to the best of our knowledge, the use of plugged/unplugged technology in the design of novel PMOmetal based catalysts in which the chemical functionality, hydrophobic-hydrophilic balance of the catalyst, [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] and plug properties could be controlled in catalytic applications has been underdeveloped. In this line and considering the advantages of using Ru species, here, we report the preparation of a series of Ru-based catalysts through the immobilization of perruthenate anions into the mesochannels of plugged/unplugged bifunctional PMOs (Ru@BFPMOs) containing imidazolium and ethylene or phenylene bridges, and their application in the aerobic oxidation of a wide range of alcohols.…”
Section: Introductionmentioning
confidence: 99%